Technology pedagogical activities on the formation of special motor skills of future teachers of physical education facilities fitness. - Tvelina A.О (Kharkov National Pedagogical University, 2011)
Reviewed the scientific and practical problems of integration of technology into the fitness training of future teachers of physical culture. The technological design algorithm by means of physical training fitness. A list of stages in a strict logical sequence: diagnostic, pre-project, projecting; realizable; control and corrective. It is noted that educational activities include: development methodology and software content of physical education students, monitoring the effectiveness of the system classes. We recommend the learning process in groups to systematize physical training with curriculum development and the location of the training material in strict logical sequence.